(-11)-w=(-36)

Simple and best practice solution for (-11)-w=(-36) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-11)-w=(-36) equation:


Simplifying
(-11) + -1w = (-36)
-11 + -1w = (-36)
-11 + -1w = -36

Solving
-11 + -1w = -36

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + -1w = -36 + 11

Combine like terms: -11 + 11 = 0
0 + -1w = -36 + 11
-1w = -36 + 11

Combine like terms: -36 + 11 = -25
-1w = -25

Divide each side by '-1'.
w = 25

Simplifying
w = 25

See similar equations:

| 4x-3-7=-27 | | x-(-15)=10 | | 2y-20=35 | | 4x+7+2x=-5x | | -8(9k+7)=15+3k | | 6x-8x+10=9x+19+13 | | r+8=22 | | 5x+2(x-3)+2x=6x+3(x+2)-4+x | | x+y-24=0 | | 12m=240 | | -12x-2y=-54-3x | | Kx+13-8x=-1 | | -7d-2d=-33 | | -2x+3=.5x+3 | | 2x^2=7x-29 | | 17+a=8 | | 3x-7y=6-5y | | 20n=180 | | 1=X-2x^2 | | 3d=9d-9 | | 29-3c=9(7c+2) | | 6=7y+3 | | 6r-12=3+7r | | -20b=280 | | 345-4532x=12 | | 3y+2-4=6 | | 8x=16x+24 | | 2(6-2y)+4y=12 | | -5(1+6r)=22 | | 60*60*0+1= | | 22+8p=5p+4(p+4) | | 130.00=.80x+18 |

Equations solver categories